Stroke Iskemik dengan Hemiparesis Sinistra pada Pasien Laki-Laki Usia 54 Tahun : Laporan Kasus - Ditya Ananda Safira; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2026)
Ischemic stroke is an acute neurological condition requiring rapid onset-time assessment because reperfusion therapy is only beneficial in selected patients within a specific therapeutic window. This case report discusses ischemic stroke with left hemiparesis in a 54-year-old male patient presenting outside the reperfusion therapy window. The patient arrived at the emergency department on September 1, 2024, at 13:31 Western Indonesian Time with left arm and leg weakness, dysarthria, left tongue deviation, and swallowing difficulty. Symptoms began on August 30, 2024, at approximately 09:00, resulting in an estimated onset-to-door time of 52 hours and 31 minutes. Blood pressure on arrival was 157/108 mmHg. A non-contrast head CT scan showed a hypodense lesion in the right temporal lobe, supporting ischemic stroke. Reperfusion therapy was not performed because the patient presented beyond the therapeutic window. Management included antiplatelet therapy, antihypertensive therapy, dysphagia screening using the water swallow test, inpatient physiotherapy, and home exercise education. After seven days of hospitalization, the patient was discharged in stable condition with compos mentis consciousness, GCS 15, left-sided motor strength of 5/5, improved dysarthria, improved tongue deviation and swallowing ability, and independent ambulation. Discharge medications included amlodipine 10 mg once daily and aspirin 80 mg once daily. This case emphasizes the importance of onset documentation, swallowing assessment, early rehabilitation, and secondary prevention in ischemic stroke.